1995
DOI: 10.1111/j.1365-2362.1995.tb01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐operative erythropoiesis is limited by the inflammatory effect of surgery on iron metabolism

Abstract: The decrease in haemoglobin concentration commonly observed after major surgery is usually corrected by red cell transfusions or oral iron medication. The increased awareness of blood-transmissible diseases has led to the restrictive use of homologous blood and to interest in alternatives for correcting anaemia. We investigated the pathophysiology of postoperative anaemia by studying variables of erythropoiesis, iron metabolism, and inflammation in 48 consecutive patients who underwent total hip replacement. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 31 publications
3
65
1
4
Order By: Relevance
“…Studies on less severe degrees of postoperative anemia have found that correction of the anemia is slow, owing to the inflammatory effects of surgery on iron metabolism and erythropoietin response to anemia. 7,8 In the observational study by Biesma et al, which included orthopedic surgery patients without preexisting anemia (average Hb = 141 ± 11 g·L -1 ) who developed postoperative anemia with an average Hb of 111 ± 13 g·L -1 , there was no correction of anemia by one-week ) rise 10 ± 9 12 ± 6 14 ± 10 6-week Hb (g·L after surgery, while by two and six weeks after surgery there was a one-third and two-thirds correction of anemia, respectively. 8 A similar study by van Iperen et al had similar findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on less severe degrees of postoperative anemia have found that correction of the anemia is slow, owing to the inflammatory effects of surgery on iron metabolism and erythropoietin response to anemia. 7,8 In the observational study by Biesma et al, which included orthopedic surgery patients without preexisting anemia (average Hb = 141 ± 11 g·L -1 ) who developed postoperative anemia with an average Hb of 111 ± 13 g·L -1 , there was no correction of anemia by one-week ) rise 10 ± 9 12 ± 6 14 ± 10 6-week Hb (g·L after surgery, while by two and six weeks after surgery there was a one-third and two-thirds correction of anemia, respectively. 8 A similar study by van Iperen et al had similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In the observational study by Biesma et al, which included orthopedic surgery patients without preexisting anemia (average Hb = 141 ± 11 g·L -1 ) who developed postoperative anemia with an average Hb of 111 ± 13 g·L -1 , there was no correction of anemia by one-week ) rise 10 ± 9 12 ± 6 14 ± 10 6-week Hb (g·L after surgery, while by two and six weeks after surgery there was a one-third and two-thirds correction of anemia, respectively. 8 A similar study by van Iperen et al had similar findings. 7 In a randomized controlled study examining treatments for postoperative anemia (see below for details of this study), Madi-Jebara et al found that, in their control group in whom the average postoperative Hb was 108 ± 13 g·L -1 , there was no correction of anemia by two-weeks after surgery, and there was only a one-third correction of anemia at four-weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is evidence that the characteristics of postoperative anemia are more similar to those of the anemia from chronic disease than from iron deficiency [19,20]. This kind of anemia is observed in patients with inflammatory disorders and malignancies: it is characterized by a decrease in the serum levels of iron and transferrin, by transferrin saturation despite adequate iron stores, and by a reduction in erythropoiesis [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…7 Transfusion Alternatives in Transfusion Medicine VOLUME 6 NUMBER 8,9 Hence, FID is a clinical situation where the iron store in the bone marrow macrophages is normal, but this iron is not available for erythropoiesis, due to an alteration of its release from the macrophages. Also, intestinal iron absorption is inhibited, due to a reduction of its release through the enterocyte basolateral membrane.…”
Section: Surgery and Erythropoiesismentioning
confidence: 99%